A comparison on the effect of 20mg Doxycycline versus placebo in the treatment of chronic periodontitis following scaling and root planning (SRP) - Khoshkhoonejad AK; Mohseni Salehi Monfared SH; Hassanjani Roshan HR (Tehran University of Medical Sciences, 2004)
Statement of Problem: Chronic periodontitis is one of the most prevalent periodontal diseases in the world"nwhich may be treated through surgical or non-surgical approaches."nPurpose: The aim of this study was to compare the efficacy of Doxycycline and placebo following SRP in"nnon-surgical treatment of chronic periodontitis."nMaterials and Methods: This double blind interventional study was conducted on patients attended to the"nperiodontology department of Tehran faculty of dentistry from 2002 to 2003. After SRP, 22 cases and 23"ncontrols were received Doxycycline and placebo, 20 mg twice a day for 3 months, respectively. Bleeding on"nprobing (BOP), pocket depth (PD)<6mm and PD>7mm, and also clinical attachment level (CAL)<6mm and"nCAL>7mm in cases and controls after 3 and 6 months were compared by student t-test."nResults: BOP after 3 and 6 months in Doxycycline recipients following SRP were significantly lower than in"nplacebo recipients (P^0.007 and P=0.045 respectively). PD<6mm, PD>7mm, CAL<6mm and CAL>7mm in 3"nand 6 months after SRP in cases were much lower than controls."nConclusion: This study showed that the administration of Doxycycline for 3 months after SRP resulted in"nimprovement of clinical indices as compared with SRP alone. Therefore, Doxycycline administration is"nrecommended for chronic periodontitis treatment after SRP.